IMPLIED FACTORS IN THE MODIFICATION OF STEREOTYPES: ENDOGENOUS AND EXOGENOUS VARIABLES - Vázquez Rodríguez, Carolina; Martínez Martínez, Mª del Carmen (Anales de Psicología / Annals of Psychology, 2008)
This paper analyzes the effects of different factors implied in stereotype change. Leaving of the sociocognitive models, two types of factors are considered: exogenous and endogenous. As endogenous factors, that the perceiver, we focus on information processing, the motivation, the threat perception, the perceived typicality and the variability. As exogenous factors, the situation, the type of information offered to the individuals and the different forms of measure and evaluate the stereotype change are commented. Although in some cases the conclusions about the influence of certain variables are unanimous, in others studies the results are opposite and don’t allow the comparison since the used procedures, the stimuli and the measures to evaluate the change are very different. The article defends the necessity of unanimity in the measure forms and the advantage that it would suppose the use of investigations with a model pre-test post-test.